Unique molecular architecture of silk fibroin in the waxmoth, Galleria mellonella - Zurovec, Michal; Sehnal, Frantisek (The Journal of biological chemistry, 2002)
Proteins of silk fibers are characterized by reiterations of amino acid repeats. Physical properties of the fiber are determined by the amino acid composition, the complexity of repetitive units, and arrangement of these units into higher order arrays. Except for very short motifs of 6-10 residues, the length of repetitive units and the number of these units concatenated in higher order assemblies vary in all spider and lepidopteran silks analyzed so far. This paper describes an exceptional silk protein represented by the 500-kDa heavy chain fibroin (H-fibroin) of the waxmoth, Galleria mellonella. Its non-repetitive N-terminal (175 residues) and C-terminal (60 residues) parts, the overall gene organization, and the nucleotide sequence around the TATA box show that it is homologous to the H-fibroins of other Lepidoptera. However, over 95% of the protein consists of highly ordered repetitive structures that are unmatched in other species. The repetitive region includes 11 assemblies AB(1)AB(1)AB(1)AB(2)(AB(2))AB(2) of remarkably conserved polypeptide repeats A (63 amino acid residues), B(1) (43 residues), and B(2) (18 residues). The repeats contain a high proportion of Gly (31.6%), Ala (23.8%), Ser (18.1%), and of residues with long hydrophobic side chains (16% for Leu, Ile, and Val combined). The presence of the GLGGLG and SSAASAA(AA) motifs suggests formation of pleated beta-sheets and their stacking into crystallites. Conspicuous conservation of the apolar sequence VIVI followed by DD or ED is interpreted as indicating the importance of hydrophobicity and electrostatic charge in H-fibroin cross-linking. The environment of G. mellonella larvae within bee cultures requires continuous production of silk that must be both strong and elastic. The spectacular arrangement of the repetitive H-fibroin region apparently evolved to meet these requirements.
Keywords: Fibroins; Models, Genetic; Molecular Sequence Data; Protein Structure, Tertiary; Sequence Analysis, DNA; modely genetické; Tissue Distribution; Southernův blotting; sekvence aminokyselin; Models, Molecular; DNA, Complementary; Protein Binding; DNA; Moths; Silk; Blotting, Southern; Amino Acid Motifs; Codon; Lepidoptera; aminokyselinové motivy; hedvábí; Transcription, Genetic; RNA; genetická transkripce; můry; polymerázová řetězová reakce s reverzní transkripcí; Base Sequence; sekvence nukleotidů; molekulární modely; komplementární DNA; zvířata; tkáňová distribuce; Amino Acid Sequence; hmyzí proteiny; vazba proteinů; kodon; fibroiny; northern blotting; sekvenční analýza DNA; Reverse Transcriptase Polymerase Chain Reaction; molekulární sekvence - údaje; sekvenční homologie aminokyselin; Blotting, Northern; Insect Proteins; terciární struktura proteinů; Sequence Homology, Amino Acid; Animals